Supply chain resilience reactive strategies for food SMEs in coping to COVID-19 crisis - Ali, Mohd Helmi; Suleiman, Norhidayah; Khalid, Norlin; Tan, Kim Hua; Tseng, Ming-Lang; Kumar, Mukesh (Elsevier, 2021)
Background: The ability of small- and medium-sized enterprises in the food industry (FSMEs) in cultivating resilience against the COVID-19 pandemic is vital food security. However, there is limited supply chain resilience literature to guide FSMEs in overcoming disruptions caused by pandemic. Scope and approach: This review aims to provide a broad view of SCRes reactive strategies for FSMEs in dealing with crises in the context of COVID-19. Attention is given to the literature on resilience in other types of supply chain and situated in the context of food settings. The factors are monitored or controlled to contribute to FSME resiliency. Key findings and conclusion: Four quadrants, i.e., (1) rapid with low cost, (2) rapid with high cost, (3) slow with low cost and (4) slow with high cost, are offered based on the limitations and the time needed to react, and the strategies of each quadrant are explained in depth. This review also provides a better understanding of and guidance on reactive strategies for SCRes as options for FSMEs in dealing with the COVID-19 pandemic. This review suggests future directions as extensions based on the logical flow of this review.